The Americas (Cambridge)
The Americas has been one of the principal English-language journals of Latin American history since 1944. Articles and reviews in history and ethnohistory about all geographical regions of the Americas and their Iberian background are included. Topics dealing with the economic, political, cultural, social, religious, diplomatic or intellectual history of Latin America.
Keywords: History